Vila Sésamo: o contexto político e educacional das duas edições audiovisuais educativas brasileiras - Santos, Ana Carolina Franco dos [UNESP] (2015)
In times of digital and convergent media, television is still a means of comprehensive and predominant communication between the popular social layers. Historically, TV shows programs that affect social coexistence, or influence of many viewers view of reality. In 1972, Sesame Street premiered on Brazilian TV as an educational program with great ratings success. The educational series is a version of Sesame Street series, produced in the United States for nearly half a century, which preserves a significant audicence among children. In Brazil, the program was produced by a parthership between Globo and TV Cultura of São Paulo and was displayed by the two broadcasters. The partnership lasted until 1974 when the Globe took over production and ran until 1977, when it was taken down because producing was too expensive. Almost four decades after the end of Vila Brazilian Sesame, TV Cultura decided to relaunch the program in late 2007, with the purpose of strengthening the network in the segment of children's programming. This research has the children's programming. This research has the children's program Sesame Street as objects of study taking as empirical material the content carried by the programs in the differents periods in which they were displayed, trying to verify the educational potential series at different times in our history. We will use as a methodology content analysis, establishing a qualitative and quantitative analysis, coding and interprets the program cut, as well as checks that the formats found corresponded to the educational needs of children viewers. After listed the frames of the two Brazilian seasons analyze which axes of early childhood education were worked out in each frame and the importance of learning in the development of children in age from early childhood education